Mengembangkan Model Pengukuran dan Struktural untuk Menilai Interrelasi Pengetahuan dengan Akhlak Siswa - Zurqoni Zurqoni (FENOMENA, 2017)
Moral in the context of school education management is essential, and execution of education of moral cannot be separated from the quality of learning and teaching, and assessment system. The application of assessment of moral knowledge and moral behavior in Madrasah Aliyah (MA) is still conventional and partial. The purpose of this research is: (a) to develop an assessment model of moral applied to assess students’ moral in Madrasah Aliyah; and (b) to find out the influence of students’ knowledge of moral on their own moral. This research produces a measurement model in the form of an internal structure consisting of dimensions of moral measurement, and a structural model relating moral with the knowledge of moral.This research applies research and development model. The subjects are students  of MAs. Data analysis utilizing Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). CFA applied to analyze conformity of measurement model, while SEM applied to analyze conformity of structural model using software LISREL 851. Conformity of measurement and structural model based on the criteria of r-value >0.05, Root Mean Square Error of Approximation (RMSEA) < 0.08, and Goodness of Fit Index  (GFI)  > 0.90.The result of this development research can be concluded as follows. The internal structure of assessment model of learning and teaching including willingness, conscience, value, attitude and moral behavior dimensions is considered as a good assessment model to assess students’ moral in Madrasah Aliyah. It is based on the result of  CFA, namely low factor loading value 0.39 (λ > 0.30), r-value = 0.0804 > 0.05; RMSEA = 0.074 < 0.08; and GFI= 0.98 > 0.90. The structural model relating moral and knowledge is regarded as a good model based on r-value = 0.08207 > 0.05; RMSEA= 0.005 < 0.08; and GFI = 0.97 > 0.90. The influence of  students’ knowledge of moral  on  their own moral (γ1=0,61) are significant.